2009
DOI: 10.1021/bm9000124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polycation Molecular Weight on Poly(2-dimethylaminoethyl methacrylate)-Mediated DNA Delivery In Vitro

Abstract: Establishing clear structure-property-transfection relationships is a critical step in the development of clinically relevant polymers for nonviral gene therapy. In this study, we determined the influence of poly(2-dimethylaminoethyl methacrylate) (PDMAEMA) molecular weight on cytotoxicity, DNA binding, and in vitro plasmid DNA delivery efficiency in human brain microvascular endothelial cells (HBMEC). Conventional free radical polymerization was used to synthesize PDMAEMA with weight-average molecular weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
137
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(155 citation statements)
references
References 42 publications
(85 reference statements)
15
137
3
Order By: Relevance
“…Here we have found that none of the pDMAEMA polymers caused any substantial haemolysis against sheep red blood cells. Cytotoxicity against Caco-2 and U937 cells was similar to concentrations found for 43 kDa pDMAEMA against human brain microvascular endothelial cells 66 . Cytotoxicity against the human cell lines was also similar to the antimicrobial polymer, chitosan, against B16F10 murine melanoma cell line and the cationic reference polymer, poly(L-lysine) 69 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Here we have found that none of the pDMAEMA polymers caused any substantial haemolysis against sheep red blood cells. Cytotoxicity against Caco-2 and U937 cells was similar to concentrations found for 43 kDa pDMAEMA against human brain microvascular endothelial cells 66 . Cytotoxicity against the human cell lines was also similar to the antimicrobial polymer, chitosan, against B16F10 murine melanoma cell line and the cationic reference polymer, poly(L-lysine) 69 .…”
Section: Discussionsupporting
confidence: 66%
“…The permeabilisation of the outer membrane by pDMAEMA appears to remove the barrier for the antibiotic, In order to use pDMAEMA as an antimicrobial coating or treatment, it must be shown to be safe to humans. Reports on the cytotoxicity of pDMAEMA vary depending on the method of administration, quaternisation of the polymer, other polymers attached and size [65][66][67][68] . Moreau et al 65 found that pDMAEMA caused little or no haemolysis to human red blood cells however, when injected intravenously into the tail vein of rats caused death at 5.1 mg/kg but was tolerated at 2.1 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…pDMAEMA shows an average pK a of 7.5 [7], and is thus sufficiently protonated at physiological pH for effective polyanion complexation. Previous reports described pDMAEMA to possess a decreased proton sponge effect compared to PEI 25 kDa [8] implying alternative mechanisms of membrane interaction, such as membrane destabilization [9]. This eventually led to reduced cell death, but the polymer retained the capacity to escape from endosomes [10].…”
Section: Introductionmentioning
confidence: 95%
“…With increasing molecular weight, its transfection efficiency, complexation efficiency but also toxicity increased [10,13]. Scarce information on the performance of low molecular weight (<43 kDa) pDMAEMA is available from the literature, although such polymers could possibly be eliminated by renal excretion [9]. Therefore, a library of low molecular weight homo-pDMAEMAs with the chain length varying from 15 to 23.7 kDa was synthesized and grafted with pHEMA (poly(2-hydroxyethyl methacrylate)), resulting in water soluble linear diblock copolymers with a total Mw below 40 kDa.…”
Section: Introductionmentioning
confidence: 99%
“…(Layman et al, 2009) Two groups (Coll et al and Wurm et al) have independently fractionated a commercial broadly-polydisperse linear PEI (l-PEI) and assayed the individual fractions for transfection efficacy. They both reported that fractions below 4 kDa show little transfection activity and little toxicity, and fractions above 20 kDa show little activity but high toxicity, with a maximum transfection efficiency at ca.…”
Section: Introductionmentioning
confidence: 99%